2022
DOI: 10.1111/jcms.13328
|View full text |Cite
|
Sign up to set email alerts
|

Feeling the Heat: Emotions, Politicization, and the European Union

Abstract: For over a decade, scholars of European studies have been studying a phenomenon referred to as the politicization of the European Union, usually defined as the intensification of a political debate, the polarization of opinions, and public resonance. This article extends existing explanatory models by offering a systematic theorization of the role of emotions in EU politicization to establish that emotions are integral to every step of the process. First, they are prerequisites as actors and audiences need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…As we have argued, national governments have to (re)construct EU narratives when talking about the EU and European crises, and to make these issues understandable to their public they will need to connect these stories with their national contexts. Crucially, crises coincide with spikes in EU politicization and emotional upheaval and actors can utilize the latter for political mobilization (Gellwitzki & Houde, 2022). Especially emotional stories about Europe can rally support to alleviate the population's uncertainty and anxieties in times of crises; in fact, EU narratives become more affectively appealing when the utopian future they promise appears increasingly unlikely (Kølvraa, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we have argued, national governments have to (re)construct EU narratives when talking about the EU and European crises, and to make these issues understandable to their public they will need to connect these stories with their national contexts. Crucially, crises coincide with spikes in EU politicization and emotional upheaval and actors can utilize the latter for political mobilization (Gellwitzki & Houde, 2022). Especially emotional stories about Europe can rally support to alleviate the population's uncertainty and anxieties in times of crises; in fact, EU narratives become more affectively appealing when the utopian future they promise appears increasingly unlikely (Kølvraa, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The study of affect and emotions in political discourse is not novel; research on populism (Browning, 2019;Homolar & Löfflmann, 2021;Widmann, 2021) or referendum campaigns (Atikcan, 2015;Atikcan et al, 2020) for instance has been demonstrating their role in framing issues to appeal to the population. Parallel to that, research on the EU's politicization has shown that actors and the public increasingly talk about the EU in times of crisis (De Wilde & Zürn, 2012;Hutter & Kriesi, 2019;Rauh et al, 2020), implying a heightened emotionality of European issues (Gellwitzki & Houde, 2022). However, in both strands of research less attention has been paid to the general Gefühlspolitik in the EU, or put differently, how actors are influenced by affective dynamics themselves or how they deliberately invoke emotions and develop affective strategic narratives to reach political objectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some countries implemented new rules to prevent migrants from entering their country (Dingott Alkopher, 2018), others gathered resources to welcome and integrate incoming refugees (Gazit, 2019; Gellwitzki, 2022), and many strongly criticized the EU for its management of the crisis. Political crises such as the so‐called migration crisis always entail emotional turmoil (Ejdus, 2018; Gellwitzki & Houde, 2022a; Homolar & Scholz, 2019), and the EU and its member states' reactions can be interpreted as attempts to cope with the existential anxieties they provoked. This anxiety management manifested in different ways, as is illustrated by contrasting the migration‐hostile reactions from countries like the United Kingdom and Hungary with the unique response from the German government (Dingott Alkopher, 2018).…”
Section: Ontological Security Narratives and Political Mythsmentioning
confidence: 99%
“…Although its primary contribution is to literatures on British Euroscepticism, however, the article also speaks to scholars working beyond these confines. First, it addresses those working in EU Studies more broadly, arguing for an ‘emotional turn’ in the discipline that has already animated other Politics and International Studies research (see also Gellwitzki and Houde, 2022). As such scholars frequently attest, without recourse to emotion we are left with a rather anodyne view of politics as ‘cold, dry, uninspiring and unmoving’ (Mercer, 2006, p. 298).…”
Section: Introductionmentioning
confidence: 99%